THE PANDEMIC: A BREEDING GROUND FOR AUTHORITARIAN POWER GRABS - Zarić, Zona; Mladenović, Ivica (Bulletin of the Institute of Ethnography SASA, 2021)
This article attempts to demonstrate that the COVID-19 pandemic provided possibilities for numerous (non)democratic governments to impose new restrictions on civil liberties, persecute opponents, limit protests and introduce new mass surveillance techniques, thus turning a devastating biological virus into a damaging political virus that has markedly eroded the overall state of freedom in the world in just a few months. In countries considered non-democratic, but also in so-called democratic ones, the restriction of freedoms is justified in the name of preservation of mere biological life (zoē). This new historical event unveils the fact that the crisis has not been handled using democratic means, even in democratic states, but rather by means they have in common with all states, including the most authoritarian ones: by using tracking technologies, without any due process or control by intermediary bodies, by taking decisions by a few, and by using the urgency of the situation in order to be granted excessive powers. Using the interpretive framework of Michel Foucault, Gilles Deleuze and Giorgo Agamben, we illustrate the new direction of late capitalism and the dormant political effects of handling the health crisis.
Keywords: coronavirus, crisis, authoritarianism, power, surveillance, media, biopolitics